Soil moisture Fuzzy Estimation Approach based on Decision-Making. (May 2017) - Flores-Carrillo, Diego Alberto; Sánchez-Fernández, Luis Pastor; Sánchez-Pérez, Luis Alejandro; Carbajal-Hernández, José Juan
Abstract: This paper presents a Fuzzy Estimation Approach based on Decision Making ( FEADM ) to estimate point soil moisture, in order to develop a regional soil moisture estimate. This keeps the advantages of an automatic irrigation system but avoiding their operational complexity. In the FEADM 's first stage, the Fuzzy Analytical Process weigh five fuzzified environmental inputs used as assessment criteria. These criteria are used by a selective assessment stage, where only the relevant criteria for each alternative are assessed. As result, the best assessments of each alternative and the best assessed alternative are obtained. In the second stage, an output membership function is assigned to every alternative for its forward aggregation and defuzzification. This process reaches a soil moisture estimate. Unlike other models, FEADM allows estimating a quantitative value from a decision making process. Furthermore, its computational cost is lower than conventional fuzzy estimation models due to the selective assessment. Highlights: A Fuzzy Estimation Approach based on Decision Making ( FEADM ) is proposed. The point soil moisture estimate allows a regional soil moisture estimation. The proposed FEADM consists of a decision making and a fuzzy estimation stage. Soil moisture levels are assessed regarding to current weather conditions. A point soil moisture estimate is derived from the assessed alternatives.